Five depictions of the circumcision of Jesus Christ from the Croatian sacral heritage : Pet primjera obrezanja Isusa Krista iz hrvatske sakralne baštine - Čulina, Tatjana (Array, 2021)
Male circumcision has been perceived differently in different cultures. In modern times, if it is a non-medical indication, circumcision becomes the starting point of many ethical and other discussions. Its rootedness in Christianity is fixed, among other things, in sacral art and iconography. This article presents five sacral images of the Circumcision of Christ from the holdings of the Croatian sacral heritage with the aim of noticing their iconographic and sacral-medical values. In this article, it is presented the results of field research related to the identification and medical-iconographic presentation of the motive for the circumcision of Jesus Christ in the area of the northern and central Adriatic coast. Five such paintings have been recorded and will be described and compared with similar works by European masters. These are the works of Venetian and Central European provenance and were created between the 16th and 18th centuries. The basic traditional Jewish iconography is visible in all the paintings but modified according to current religious standards. These depictions from the area of Croatia contextualizing and filling in the gaps in verbal records on this topic in our region fit Croatia into an undoubted component of the European Judeo-Christian heritage and when it comes to rare iconographic depictions.